Criofolinine and vernavosine, new pentacyclic indole alkaloids incorporating pyrroloazepine and pyridopyrimidine moieties derived from a common yohimbine precursor - Nge, C.E.; Gan, C.Y.; Lim, K.H.; Ting, KN.; Low, Y.Y.; Kam, T.S. (American Chemical Society, 2014)
Two new indole alkaloids characterized by previously unencountered natural product skeletons, viz., criofolinine (1), incorporating a pyrroloazepine motif within a pentacyclic ring system, and vernavosine (2, isolated as its ethyl ether derivative 3, which on hydrolysis regenerated the putative precursor alkaloid 2), incorporating a pyridopyrimidine moiety embedded within a pentacyclic carbon framework, were isolated from a Malayan Tabernaemontana species. The structures and absolute configuration of these alkaloids were determined on the basis of NMR and MS analysis and confirmed by X-ray diffraction analysis.